How Entrepreneurship Education and Creativity Shape Entrepreneurial Intention: The Role of Self-Efficacy? - Yuniar, Fira; Dewantara, Hajar; Nurhayani, Nurhayani; Haruna, Hasisa; Adelia, Nur (Pinisi Journal of Entrepreneurship Review, 2025)
This study examines the effects of entrepreneurship education and creativity on entrepreneurial intention by considering the role of self-efficacy. A quantitative explanatory design was employed, using data collected from 100 respondents selected through proportional random sampling from a population of 492 students. The research instrument was a five-point Likert scale questionnaire, and the data were analyzed using descriptive statistics, hypothesis testing, and path analysis. The findings indicate that entrepreneurship education has a significant positive effect on entrepreneurial intention, although its effect on self-efficacy is not statistically significant. In contrast, creativity has a significant positive effect on both entrepreneurial intention and self-efficacy. The indirect analysis further suggests that self-efficacy plays an important explanatory role, particularly in strengthening the contribution of creativity to entrepreneurial intention. These findings imply that entrepreneurship education alone may not be sufficient to build strong entrepreneurial confidence unless it is accompanied by learning experiences that foster creativity, opportunity recognition, and problem-solving capacity. This study highlights the importance of integrating entrepreneurship education with creativity development to cultivate stronger entrepreneurial intention and more robust self-belief. The findings offer practical implications for higher education institutions in designing entrepreneurship programs that are more experiential, confidence-building, and innovation-oriented.